A sustainable approach on biomining of low-grade bauxite by P. simplicissimum using molasses medium - Shah, Syed Sikandar [UNESP]; Palmieri, Mauricio Cesar; Sponchiado, Sandra Regina Pombeiro [UNESP]; Bevilaqua, Denise [UNESP] (Springer Nature, 2022)
In order to find a sustainable and low-cost alternative route to the traditional recovery of aluminum, the filamentous fungus Penicillium simplicissimum was evaluated for aluminum recovery from low-grade bauxite ore. The oat-agar medium was carefully chosen as the foremost solid medium for fungal sporulation due to lower cost, ease in preparation, and high spore production in a short incubation time. To examine the acid production capability in submerged fermentation, P. simplicissimum was inoculated in a medium augmented with glucose and molasses as an energy source. High-performance liquid chromatography (HPLC) technique was used for the determination of the produced organic acids. Three different bioleaching approaches were evaluated using 1% bauxite pulp density. The culture containing P. simplicissimum spores grown in a medium supplemented with molasses leached 86.6% Al in the direct two steps on the fifth day, 56.5% in the direct one step on the fourth day, and 71.7% in the indirect bioleaching on the fourth day, while in the controlled sterile flasks, Al leaching was almost negligible. A maximal amount of Al was leached by the fungal strains using low-cost molasses as a substrate.
Keywords: Aluminum recovery; Biogenic acids; Bioleaching; Fermentation; Filamentous fungus